2021
DOI: 10.3389/fphys.2021.780255
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis and Chlorantraniliprole Trigger the Expression of Detoxification-Related Genes in the Larval Midgut of Plutella xylostella

Abstract: Background: Diamondback moth (DBM), Plutella xylostella (L.), has developed resistance to many insecticides. The molecular mechanism of DBM resistance to Bt-G033A combined with chlorantraniliprole (CL) remains undefined.Methods: In this study, field-resistant strains of Plutella xylostella to three pesticides, namely, Bacillus thuringiensis (Bt) toxin (Bt-G033A), CL, and a mixture of Bt + CL, were selected to evaluate the resistance level. Additionally, transcriptomic profiles of a susceptible (SS-DBM), field-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…(Lepidoptera: Plutellidae) [8]. It is worth noting that high enzymatic activity does not always associate with resistance to individual insecticides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Lepidoptera: Plutellidae) [8]. It is worth noting that high enzymatic activity does not always associate with resistance to individual insecticides.…”
Section: Resultsmentioning
confidence: 99%
“…It is also provided by the ABC transporters, involved in the excretion of metabolites from the insect body, which were formed in the previous step [7]. Hydrolysis of insecticides by esterases is an important biochemical mechanism for the development of insecticide resistance that is common to several classes of chemical compounds [8][9][10]. Acetylcholinesterase (EC 3.1.1.7, AChE) is a serine esterase of the α-, βhydrolase family.…”
Section: Introductionmentioning
confidence: 99%
“…In studies on Plutella xylostella (diamondback moth) strains resistant to chlorantraniliprole and to Bacillus thuringiensis plus chlorantraniliprole, the expression of numerous potential genes, including cytochrome P450, glutathione S ‐transferase (GST), carboxylesterase and acetylcholinesterase, were found to be increased (Shabbir et al . 2021). A molecular docking study indicated that pesticides could potentially enter a cavity within one of the four subdomains of CAT, highlighting specific amino acid residues and hydrogen bonds involved in CAT–pesticide interactions (Tan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Entomological Research 54 (2024) e12710 (GST), carboxylesterase and acetylcholinesterase, were found to be increased (Shabbir et al 2021). A molecular docking study indicated that pesticides could potentially enter a cavity within one of the four subdomains of CAT, highlighting specific amino acid residues and hydrogen bonds involved in CAT-pesticide interactions (Tan et al 2014).…”
Section: Catalases In Tenebrio Molitormentioning
confidence: 99%
“…However, minimal studies on cuticular resistance in invasive insects such as P. xylostella revealed a significant difference in cuticular microRNAs between the chlorantraniliprole resistance population and the susceptible population. They give insight into cuticular alteration during the development of resistance ( Zhu et al, 2017 ; Shabbir et al, 2021 ). There is evidence of cuticular resistance in H. armigera , which successfully prevented deltamethrin adsorption in the body by generating thicker cuticles in resistant individuals compared to susceptible individuals, where insecticide percolation was substantially higher ( Ahmad et al, 2006 ).…”
Section: Resistance In Invasive Insectsmentioning
confidence: 99%